Conformational preferences for isomeric N,N′-bis(pyridin-n-ylmethyl)ethanedithiodiamides, n = 2, 3 and 4: a combined crystallographic and DFT study - Zukerman-Schpector, J.; Madureira, L.S.; Poplaukhin, P.; Arman, H.D.; Miller, T.; Tiekink, Edward R.T. (De Gruyter, 2015)
Crystal structure analysis of the isomeric N,N′-bis(pyridin-n-ylmethyl)ethanedithioamides, n = 2 (1), 3 (2) and 4 (3), show a planar conformation for 1 and conformations whereby the pyridyl rings lie orthogonal and to either side of the central residue for each of 2 and 3. The universal adoption of the all ZZ conformation about the central C-N bonds, which have double bond character, is ascribed to the presence of intramolecular N-H...S hydrogen bonds that close S(5) rings. The gasphase geometry optimised structure for 1 is the same as the experimental structure which features intramolecular amine-N-H...N(pyridyl) hydrogen bonds. The open structures found for 2 and 3 differ from the somewhat flattened optimised structures. Systematic variations in the geometric parameters characterising the central C2N2S2 residue, in particular the double-bond character of the C-N bond and the elongation of the central C-C bond are shown by theory to be due to conjugative nN → π∗C=S interactions and nS → σ∗C-C hyperconjugation, respectively.